The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/bf02936373
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of complement C3, C4, and factor B molecules in human bile

Abstract: We performed molecular analysis of complement components (C3, C4, and factor B) in human bile by sodium dodecyl sulfate-polyarylamide gel electrophoresis (SDS-PAGE) and immunoblotting. Complement C3 was detected as a molecule composed of a 115-kDa alpha-chain linked to a 70-kDa beta-chain by disulfide bonds, and C3 levels ranged from 45 to 650 micrograms/ml (n = 15). C4 was detected as a triple chain (98-kDa alpha-chain, 73-kDa beta-chain, and 33-kDa gamma-chain) molecule linked by disulfide bonds, and C4 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…However, the presence of IgG AMA, as well as functional complement, in bile could have a major effect on the inflammatory process. 7,53 The presence of disparate IgA and IgG epitopes on the same molecule FIG. 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of IgG AMA, as well as functional complement, in bile could have a major effect on the inflammatory process. 7,53 The presence of disparate IgA and IgG epitopes on the same molecule FIG. 5.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatobiliary system and the exocrine pancreas also secrete large amounts of active complement components into the gastrointestinal tract (17,18). Intestinal epithelial cells (IECs) locally synthesize and secrete complement components into the lumen (19 -22).…”
mentioning
confidence: 99%
“…Previous studies have reported that intestinal epithelial cells are the local source of complement components (4,5) and that these complement components are also supplied into the gut lumen from the exocrine pancreas and bile system. (6,7) Therefore, blockade of the complement cascade at the C5 step may modulate the composition of the gut microbiota. The gut microbiota are an important factor which can affect colitis development.…”
Section: Discussionmentioning
confidence: 99%
“…(4,5) Complement components are also supplied into the gut lumen from the exocrine pancreas and bile system. (6,7) Furthermore, previous studies have reported the deposition of complement components at the inflamed mucosa of inflammatory bowel disease (IBD) patients, suggesting that complement-mediated tissue injury is involved in the pathophysiology of IBD. (8,9) The regulatory mechanisms of complement activation are finely balanced, since overactivation of the complement system leads to tissue injury.…”
Section: Introductionmentioning
confidence: 99%